2008
DOI: 10.1093/rheumatology/ken027
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the genetic susceptibility of chronic widespread pain: the tender points in genetic association studies

Abstract: Chronic widespread pain (CWP) is a prevalent disorder associated with a low pain threshold and increased levels of psychological distress. Evidence indicates that there is a genetic component to CWP syndromes and pain sensitivity. Here we have identified and reviewed the current literature on genetic association (GA) studies of CWP and pain sensitivity by searching MEDLINE and EMBASE between January 1990 and May 2007. Of the 18 candidate genes studied to date, no definitive susceptibility genes have been ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 54 publications
1
29
0
Order By: Relevance
“…Genes that code for proteins in the opioid system (such as OPRM1) are implicated in both the processing of somatic pain and the formation of social attachments (95, 100). Polymorphisms in the μ-opioid receptor gene, d-opioid receptor subtype 1 gene, and catechol-O-methyltransferase gene were all associated with increased sensitivity to experimentally induced pain (101, 102). Mice lacking μ-opioid receptor genes exhibited less attachment-related behaviors, such as separation vocalizations and reactions to maternal cues (95).…”
Section: Multidisciplinary Research Findingsmentioning
confidence: 99%
“…Genes that code for proteins in the opioid system (such as OPRM1) are implicated in both the processing of somatic pain and the formation of social attachments (95, 100). Polymorphisms in the μ-opioid receptor gene, d-opioid receptor subtype 1 gene, and catechol-O-methyltransferase gene were all associated with increased sensitivity to experimentally induced pain (101, 102). Mice lacking μ-opioid receptor genes exhibited less attachment-related behaviors, such as separation vocalizations and reactions to maternal cues (95).…”
Section: Multidisciplinary Research Findingsmentioning
confidence: 99%
“…A number of studies have examined genetic variants for CWP. These candidate gene studies examined polymorphisms in genes involved in both the peripheral and the central nervous system 8. In particular, genes involved in neurotransmission (pathway of dopamine and serotonin9–19), and genes important for the hypothalamic–pituitary–adrenal axis have been considered 20.…”
Section: Introductionmentioning
confidence: 99%
“…This is in contrast to another study that found that the S (low expressing) allele was associated with being less sensitive to heat, cold, and pressure pain compared with the L (high expressing allele) [45,46] in healthy individuals. FM patients are reported to be more sensitive to sensory stimuli, however, and the S allele was associated with an increased risk of FM in earlier studies [19]. However, comorbid psychological traits such as depression, in which serotonin is important, may also influence pain sensitivity, making it difficult to determine the polymorphism's true effect.…”
Section: The Serotonergic Systemmentioning
confidence: 96%
“…As previously reviewed, the evidence for the involvement of 5HTTLPR in chronic widespread pain is equivocal [19]. Potvin et al [44] reported no difference in genotype frequency between FM patients (n=58) and healthy controls (n=60).…”
Section: The Serotonergic Systemmentioning
confidence: 99%
See 1 more Smart Citation